The Effect of ESG Disclosure, Green Investment, and Carbon Emission Disclosure on the Value of Energy Companies in Indonesia: Analysis for the 2019-2023 Period - Putri, Alyssa Aulya; Paramita, Veronika Santi (Sinergi International Journal of Accounting and Taxation, 2025)
This study aims to examine firm value in the energy sector during 2019-2023. Climate change remains one of the world's most urgent and long-term environmental problems. The energy sector contributes significantly to total emissions, with a high dependence on fossil fuels, particularly coal. The average enterprise value of the energy sector fluctuated from 2019 to 2023. Examination of the influence of ESG disclosure, green investment, and carbon emission disclosure on firm value in the energy sector from 2019 to 2023 is appropriately stated in this study. Climate action is now used as one of the investment considerations by investors as part of the response to the Sustainable Development Goals (SDGs). This quantitative study uses descriptive causality approaches. It uses panel data as a secondary source and examines energy firms registered on the Indonesia Stock Exchange between 2019 and 2023. A purposive sampling method is applied to select nine energy sector companies as samples. Researchers used panel data regression. The study findings show that firm value is not affected by ESG disclosure. Furthermore, firm value is positively impacted by green investment and carbon emission disclosure. ESG Disclosure, Green Investment, and Carbon Emission Disclosure simultaneously affected firm value.